Improved thermal conductivity and tailored phonon dynamics in hexagonal prism-like ZnO:Er3+ upconverting phosphor - Kalpana Singh; Kirti; Abhishek Kumar Soni (Materials Research Express)
Er ^3+ ions doped ZnO phosphors have been synthesized by using the chemical co-precipitation method. X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), UV–Visible, and Raman spectroscopy characterizations were performed for the developed phosphor. Upconversion emission spectra under 980 nm laser diode excitation show detectable Er ^3+ ion transitions in the visible colour region. The introduction of the Er ^3+ in the ZnO matrix exhibits two strong new Raman modes at 637 cm ^−1 due to 2(E _2H -E _2L ) and 830 cm ^−1 due to A _1 (TO) + E _2L , originating via tailored phonon dynamics. An unusual linewidth narrowing and blue shift of the characteristic Raman band of the wurtzite structure corresponding to the E _2H Raman mode of the ZnO: Er ^3+ phosphor has been observed. An enhanced phonon lifetime of about 1.56 $× {10}^{-12}$ s was calculated for the E _2H Raman mode. Moreover, the thermal conductivity measurement shows a noticeable increment in the ZnO: Er ^3+ (0.072 W·m ^−1 ·K ^−1 ) as compared to the ZnO (0.067 W·m ^−1 ·K ^−1 ) phosphor due to the reduced electron–phonon coupling. The synthesized ZnO: Er ^3+ phosphor may be used for upconverting and thermoelectric material development.